Sustainable finance and challenges in the Peruvian market regarding sustainability - Fernández, Mercedes (2024)
In this article, the authors explain the different sustainable financing alternatives that are being developed in Peru (i.e. green, social and sustainable bonds), as well as the main components of the carbon certificates market. The article also details some of the benefits that can be obtained through sustainable finance. Finally, the authors describe the challenges faced by Peruvian companies in terms of sustainability, as they have to implement several measures established by the European Union and the Securities and Exchange Commission, without having tax incentives or other promotional measures for the development of sustainable projects in Peru.